LEARNING TO DEVELOP STUDENTS' DEDUCTIVE SCIENTIFIC REASONING PATTERNS THROUGH SHERLOCK HOLMES NOVELS AND SHORT STORIES - Susdarwono, Endro Tri; S. Thoriqul Huda (NALAR: Jurnal Pendidikan dan Kebudayaan, 2023)
This study aims to provide a description related to learning to develop students' deductive scientific reasoning patterns through novels and short stories of Sherlock Holmes. This research is a quantitative research while the method used is semi-experimental. The quantitative approach used includes the Mann-Whitney test. The conclusions of this study are that: 1) for the Mann-Whitney test on the pre-test scores of the control group and the experimental group it was concluded that before the treatment or treatment the two groups, namely the control and the experiment, had the same ability in mastering students' deductive scientific reasoning; 2) for the Mann-Whitney test on the post-test scores of the control group and the experimental group it was concluded that after the treatment or treatment the two groups, namely the control and the experiment, had different abilities in mastering deductive scientific reasoning. Based on the two tests that there is indeed a difference between the conditions before and after being given treatment or treatment of students' mastery of deductive scientific reasoning through learning Sherlock Holmes novels and short stories.